Implementasi Sistem Hybrid Photovoltaic–Thermoelectric Generator sebagai Sumber Energi Listrik pada Kapal Nelayan - Maulidiah Rahmawati; Faiq Rasyad Hazami (Fakultas Teknik dan Ilmu Kelautan, Universitas Hang Tuah, 2025)
Electrical energy systems on small-fishing-vessels are still predominantly dependent on fossil-fuel-based generators, resulting in high fuel consumption and environmental emissions. This study aims to implement a hybrid photovoltaic–thermoelectric generator (PV–TEG) system as an additional electrical energy source for fishing-vessels by utilizing solar energy and diesel engine waste heat. The research employed a quantitative experimental approach through the development of a hybrid prototype consisting of a 20 WP photovoltaic module, four SP1848-27145-SA thermoelectric generator modules, a buck-boost converter, and a 12 V battery. Field testing was conducted on a diesel-powered fishing-vessel in the Suramadu coastal area, Surabaya, under two experimental scenarios with a 6-hour observation period from 09:00 to 15:00 WIB. The evaluated parameters included photovoltaic voltage, thermoelectric generator voltage, temperature difference (), and hybrid system output power. The results showed that the photovoltaic system produced an average voltage of 20.00 V during the first test and 20.63 V during the second test. The thermoelectric generator achieved a maximum output voltage of 6.3 V at a temperature difference of 47.3°C. The implementation of the hybrid PV–TEG system increased output power from 14.46 W to 17.28 W during the first test, representing a 19.50% improvement, while during the second test the output power increased from 41.15 W to 48.72 W, corresponding to an 18.40% improvement. These findings demonstrate that the integration of photovoltaic and thermoelectric generator systems can improve the continuity of electrical power supply on fishing-vessels through simultaneous utilization of solar energy and diesel engine waste heat.